1990
DOI: 10.1111/j.1365-2125.1990.tb03741.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the 5‐HT3 receptor antagonist ICS 205‐930 on fat‐delayed gastric emptying and antral motor activity.

Abstract: 1. The selective 5‐HT3 receptor antagonist, ICS 205‐930 (Sandoz), has been reported to have potent effects on gastric smooth muscle in vivo and to enhance gastric emptying in animals and in man. 2. This study investigated the effects of ICS 205‐930 on fat‐delayed gastric emptying of a semisolid meal and antral motor activity in humans. 3. Twelve healthy men participated in each of three studies in which 10 or 20 mg of ICS 205‐930 or placebo were infused i.v. in a random double‐blind fashion. Gastric emptying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
1
13
1
Order By: Relevance
“…On the other hand, Talley et al29 reported that ondansetron, a selective 5-HT 3 RA, did not significantly alter small intestine transit and oral to cecal transit time in healthy volunteers. Troisetron, a selective 5-HT 3 RA, has been found to either modestly increase gastric emptying or reduce it in healthy volunteers 30. The action of 5-HT 3 RAs to modify contraction-relaxation responses would be dependent on the relative balance of excitatory-inhibitory tone 17,23.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Talley et al29 reported that ondansetron, a selective 5-HT 3 RA, did not significantly alter small intestine transit and oral to cecal transit time in healthy volunteers. Troisetron, a selective 5-HT 3 RA, has been found to either modestly increase gastric emptying or reduce it in healthy volunteers 30. The action of 5-HT 3 RAs to modify contraction-relaxation responses would be dependent on the relative balance of excitatory-inhibitory tone 17,23.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in animal studies, tropisetron abolishes various intestinal effects of 5‐HT 4 agonists 36 , 47–49 and, in healthy volunteers, Stacher et al . found a further increase in fat‐induced delayed gastric emptying by intravenous tropisetron, 20 mg, compared to 10 mg which did not differ from placebo 21 . In contrast to tropisetron, ondansetron has a very weak affinity to other receptors, such as 5‐HT1c, α1 and μ opioid receptors, which is probably without any clinical relevance 5 , .…”
Section: Discussionmentioning
confidence: 96%
“…Some investigators have found an accelerated gastric emptying, 14 , 15 but others have not, 16–19 or even demonstrated an opposite effect of 5‐HT 3 receptor antagonists 20 , . 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acceleration (Buchheit et al, 1985;Akkermans et al, 1988), delay (Stacher et al, 1990), and no effect have been reported (Mawe et al, 1989;Gershon et al, 1990). In part, the different results could be explained by the nutrient content of the meal, indicating that 5-HT 3 receptors located on primary afferent nerve fibers and centrally controlled reflexes are involved (Read and G wee, 1994).…”
Section: Functional Aspect Of 5-ht-mediated Responses: Role Of 5-ht Imentioning
confidence: 99%